MENINGKATKAN KREATIFITAS ANAK USIA 4-5 TAHUN DALAM MELIPAT MELALUI MEDIA ORIGAMI DI TK IT ASSALAM PALARAN - Mariani; Arbayah; Sjamsir, Hasbi (Manajemen Pendidikan Program Doktor, 2022)
One of the problems found in Tanan Kanak is the lack of interest or interest of children in folding activities, to overcome this, so that the media used is made of origami paper material.research conducts classroom actions in order to improve children's fine motor skills in terms of folding through origami in children aged 4-5 years in Integrated Islamic Kindergarten As greetingsThe purpose of this study was to detect the ability of children's creativity, train children's fine motor flexibility, train children'shearing and experience. The design of class action research is in the form of cycles starting from the stages of planning, implementation, observation / data collection / instruments and reflection of the cycles that have been carried out in the followingresults ;p there is cycle 1 showing the value of Not Developing (BB) and Starting to develop (MB), In the 2nd cycle shows the value of developing according to expectations (BSH) and developing very well (BSB).The conclusion of this study is the improvement of children's skills in terms of folding, the result is to experience a fairly good improvement from cycle 1 and increase in cycle 2